Creating NDIS Impact - Getting the Right Mix of Choice and Control in Australia’s Disability Sector - Burrows, Matthew Scott (Curtin University, 2024)
Through interviews and surveys of people with disability, their carers and service providers, this thesis investigated the impact that decision-making structures and processes have on the involvement of consumers in governance in the disability sector in Australia. It showed how improving consumer involvement in decision-making, at the individual, organisational, and public policy levels, can improve the impact of the National Disability Insurance Scheme for people with disabilities.